Dystrophic calcinosis cutis successfully treated with extracorporeal shockwave lithotripsy. (1st December 2021) - Beatty, P.; Killion, L.; Power, R.; Roche, M.
Abstract: This case illustrates a presentation with dystrophic calcinosis cutis recalcitrant to several treatment modalities. Treatment with extracorporeal shockwave lithotripsy was initiated with near complete resolution of calcium deposits.